Leading indicator properties of corporate bond spreads, excess bond premia and lending spreads in the euro area - Elizaveta Krylova (European Central Bank (ECB), 2016)
This paper analyses leading indicator properties of a broad set of credit spreads, compiled on the basis of information from both corporate bonds and bank loans for forecasting of real activity, unemployment, inflation and lending volumes in the euro area and in five major European economies. It also introduces a set of indicators for excess bond premia, adjusting corporate bond spreads for credit risk of the issuer and the term, coupon and liquidity premia. I find that the majority of macroeconomic indicators can be better predicted by the excess bond premia compared to non-adjusted indices; the rating-adjustment and time-varying parameter estimates seem to be particularly important. Although the predictive power of lending spreads is inferior to the predictive power of the excess bond premia, the forecasting performance of models which use the information from both lending and corporate bond spreads is always superior to models using only information from one source of external funding.
Keywords: G12; C21; C22; E37; E44; 330; credit risk; excess bond return; forecasting